We care kits - Shuib, Norley; Nikmat, Azlina Wati; Mohamed, Salina; Hashim, Nurul Azreen; Ali, Nur Faizah; Nasution Raduan, Nor Jannah (Faculty of Medicine, 2021)
The COVID-19 pandemic has caused a significant burden and overutilization of the healthcare facilities in Malaysia. The country saw an exponential rise in the number of daily COVID-19 cases from 360 confirmed new cases on 1st October 2020 to 5728 new cases daily on 30th January 2021. The third wave of the pandemic saw the country clocking about 6000 to more than 24000 new cases daily beginning July 2021. Due to the worsening of the COVID-19 pandemic, CTC UiTM Sg Buloh and Hospital UiTM Puncak Alam are both involved in managing COVID-19 patients and non-COVID-19 patients referred from nearby Ministry of Health hospitals like Hospital Sg Buloh and Hospital Selayang. The workload of the UiTM healthcare professionals increased tremendously compared to the pre-COVID-19 period. The prolonged and endless battle has caused fatigue, stress, and to a certain extent, burnout among them. It could also lead to anxiety and depression.